Prevalence of Thyroid Disorder in First Trimester of Pregnancy, Study from Lumbini Province Nepal - Deepanjali Sharma; Jigyasa Subedi; Manoj Lamsal; Tara KC; Hasina Banu (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Thyroid disorder is the second most common endocrine disorder of pregnancy. The most common thyroid disorder is hypothyroidism which often goes undiagnosed during pregnancy without screening. It has inﬂuence in maternal and fetal outcome of pregnancy. The objective of this study is to determine the prevalence of thyroid disorder in the ﬁrst trimester of pregnancy. MATERIAL AND METHODS This was cross-sectional observational study conducted for a period of 6 months (Jan - June 2022) at Universal College of Medical Sciences, Bhairahawa, Nepal. All the pregnant women in their ﬁrst trimester who came for antenatal check-up in gynae OPD was included after taking consent. RESULTS Total 393 cases were evaluated. 58% were primigravida and 42% were multigravida. Mean age was 26 years with minimum 17 years and maximum 41 years. Majority of cases were of the age group 20 to 30 years 76.6%. Thyroid disorder noted in 21.3%. Hypothyroidism found in 18.6% with overt hypothyroidism in 12.8% and subclinical hypothyroidism in 5.8%. Hyperthyroidism noted in 2.7% with overt hyperthyroidism in 1.5% and subclinical hyperthyroidism in 1.2%. CONCLUSION Thyroid disorder in pregnancy in common health problem in ﬁrst trimester in pregnancy. Early diagnosis and treatment is needed to reduce complications associated with this endocrine disorder of pregnancy.